Dark-Side Personality Trait Interactions: Amplifying Negative Predictions of Leadership Performance. (May 2018) - Simonet, Daniel V.; Tett, Robert P.; Foster, Jeff; Angelback, Anastasia I.; Bartlett, Jennifer M.
Drawing on trait interaction theory and personality disorder subtypes, we examined narcissism-by-trait interactions (e.g., narcissism × antisocial tendencies) for predicting leadership performance in four independent archival samples ( N s = 285, 120, 106, 559). This study extends research on multiplicative effects of normative leader characteristics to consider how narcissism becomes particularly disruptive when combined with other extreme interpersonal tendencies. Moderated multiple regression results show interactions involving selected trait pairs varied across samples. Pooled analyses showed (a) differential generalizability across trait pairings and (b) that lower tiered managerial roles and weaker industrial contexts may release such effects. Inconsistencies suggest the need to consider sample-specific trait demands in future trait interaction research, normal, or maladaptive. All told, findings suggest that subclinical personality interactions might accelerate leader derailment, offer unique insights into leader competence, and extend trait interaction research to aberrant tendencies.